Linear disjointness preservers of operator algebras and related structures - Liu Jung-Hui (Acta scientiarum mathematicarum, 2018)
We survey some recent studies of linear zero product or orthogonality preservers between C /W∗ -algebras, their dual or predual spaces, and holomorphic disjointness preservers of C -algebras. Such maps are expected to provide algebra or linear Jordan (∗-) homomorphisms between the underlying operator algebras. We also study orthogonality preservers between Hilbert C -modules and Fourier algebras. A few open problems are stated.